Penerapan Model Pembelajaran Project Based Learning untuk Meningkatkan Kolaborasi Siswa pada Mata Pelajaran IPAS Kelas IV Aulia Cendekia Pekanbaru - Meidisa, Davia; Hariyanti, Mimi; Nafasatul Hawadis; Rosyadatul Izzati S (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Collaboration is an important skill in 21st-century learning. However, initial observations on science learning in grade IV Aulia Cendekia Pekanbaru indicate that students' collaboration skills are still low. Students are not optimal in working together, dividing tasks, expressing opinions, and actively participating in group activities. This study aims to improve students' collaboration skills through the application of the Project Based Learning model in science subjects in grade IV Aulia Cendekia Pekanbaru. This study is a Classroom Action Research (CAR) conducted in two cycles. The subjects of the study were teachers and students of grade IV Aulia Cendekia Pekanbaru, while the objects of the study were the application of the Project Based Learning model and students' collaboration skills. Data were collected through observation, performance, and documentation. Data analysis was carried out descriptively quantitatively by calculating the percentage increase in students' collaboration skills in each cycle. The results showed that students' collaboration skills before the action were 67%, increased to 76% in cycle I, and reached 94% in cycle II. Thus, the application of the Project Based Learning model can improve students' collaboration skills in science learning in grade IV Aulia Cendekia Pekanbaru